The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnins.2022.806876
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography in the Neuroimaging of Autism Spectrum Disorder: A Review

Abstract: Autism spectrum disorder (ASD) is a basket term for neurodevelopmental disorders characterized by marked impairments in social interactions, repetitive and stereotypical behaviors, and restricted interests and activities. Subtypes include (A) disorders with known genetic abnormalities including fragile X syndrome, Rett syndrome, and tuberous sclerosis and (B) idiopathic ASD, conditions with unknown etiologies. Positron emission tomography (PET) is a molecular imaging technology that can be utilized in vivo for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 182 publications
0
6
0
Order By: Relevance
“…Cerebral circulation hypoperfusion is a key problem worthy of attention, but it has been minimally studied. Low perfusion is mainly in the frontal lobe, temporal lobe, cerebellum, and limbic system (Tan et al, 2022). The common hypoperfusion brain region is basically consistent with the “social brain” region proposed by Brothers in 1990, which involves human social cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral circulation hypoperfusion is a key problem worthy of attention, but it has been minimally studied. Low perfusion is mainly in the frontal lobe, temporal lobe, cerebellum, and limbic system (Tan et al, 2022). The common hypoperfusion brain region is basically consistent with the “social brain” region proposed by Brothers in 1990, which involves human social cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a complementary search with Google Scholar was conducted to confirm that no studies were missing. Finally, we screened three of the latest review articles on the issue to ensure the full coverage of our research [16,53,54]. Altogether, we found nine potentially eligible articles [55][56][57][58][59][60][61][62][63], but only six included requisite data on striatal ROIs.…”
Section: Meta-analysismentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) studies in humans have suggested that the dysfunction of the MCL is associated with ASD [12][13][14][15]. Human positron emission tomography (PET) studies have further shown deviant dopamine signaling in ASD compared to controls, but the results have been controversial [16,17]. There is also support for dopamine dysregulation in ASD from genetic studies [18].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance spectroscopy (MRS) studies have suggested possible regional changes in GABA or glutamate levels, though findings are inconclusive 75,76 . Positron emission tomography (PET) and single photon emission computed tomography (SPECT) studies have indicated decreased serotonin receptor 5‐HT 2A binding 77 , which could inform treatment studies using medications that block 5‐HT 2A in addition to other receptors.…”
Section: Biomarkers In Autism Spectrum Disordermentioning
confidence: 99%